The secret of the rose in two poems of Sologuren: «Interludio» (Interlude) and «Rosa terrena» - Anchante Arias, Jim (2016)
This essay is an analysis of the poems «Interludio» (El morador [1944; Inhabitant]) and «Rosa terrenal» (Diario de Perseo [1948; Perseus’ diary]), included in the book Vida continua (1989; Continuous Life) of the Peruvian poet Javier Sologuren (1921-2004), who belonged to the Generación de 1945 (Generation ‘45). The theoretical framework of this analysis is the reflection of the poetic symbol of the rose, which, as we know, has one long tradition as in the Western as Oriental world. Thus, as the first poem suggests, the rose is a reflection on nature and time. In the second poem, and continuing with the existential problem of the first, it places most emphasis on the human anguish over the life and death awareness.